2021
DOI: 10.1584/jpestics.d21-017
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of residual pesticides and the quality of white clover silage are related to the types and initial concentrations of pesticides

Abstract: In order to understand the degradation of different residual pesticides of white clover silage and their influence on silage quality, three commonly used orchard pesticides with different concentrations were added to the white clover and fermented for 90 days. The results showed that the degradation rate of cypermethrin and its toxic degradation product 3-phenoxybenzoic acid (3-PBA) was the highest after silage, at different concentrations, both were 100%. The degradation rate of Tebuconazole and chloropyridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…tion of residual pesticide in white clover was observed and residues were far below the safety standards after silage fermentation. 28)…”
Section: Residues Of Pendimethalin In Green Fodder and Silagementioning
confidence: 99%
“…tion of residual pesticide in white clover was observed and residues were far below the safety standards after silage fermentation. 28)…”
Section: Residues Of Pendimethalin In Green Fodder and Silagementioning
confidence: 99%
“…Pesticide residues in green fodder are the major source of pesticides in silage. In addition to the great health risk to ruminants and humans, the types and initial concentrations of pesticides affect the fermentation quality of silage (Ge et al, 2021 ). Zhang, Yu, et al ( 2017 ) found that both chlorpyrifos and chlorantraniliprole increased the butyric acid concentration of alfalfa silage when these two pesticides were sprayed on the surface of alfalfa before ensiling.…”
Section: Roles Of Functional Lab In Silage Prepara...mentioning
confidence: 99%
“…Synthetic nematicides are a practical and considered fast method to control parasitic nematode. In fact, the chemicals not only harm the environment but also might degrade quality of agriculture products [9]. In addition, the use of synthetic nematodes for an extended period of time will lead nematodes to develop resistance.…”
Section: Introductionmentioning
confidence: 99%